Metabolic Differences Between Shod and Barefoot Walking in Children - Shultz, S. P.; Houltham, S. D.; Kung, S. M.; Hume, P.; Fink, P. W. (International Journal of Sports Medicine, 2016)
Footwear affects the biomechanics of children’s gait; however, there has been less research addressing the energetics of walking with and without shoes. This study investigated the effects of barefoot and shod walking on metabolic parameters in children. 25 children (9.7±1.4 years) walked at a self-selected pace for 5 min on an instrumented treadmill under 2 footwear conditions (barefoot, running shoe). Vertical oscillations of centre of mass were calculated from ground reaction forces. Expired gases were collected in the last minute of each trial. Paired t-tests revealed significantly higher oxygen consumption (17.6±2.5 ml.kg−1.min−1 vs. 16.3±3.1 ml.kg−1.min−1), energy expenditure (3.25±0.86 kcal.min−1 vs. 2.97±0.68 kcal.min−1), and economy (298.2±47.5 ml.kg−1.km−1 vs. 275.9±56.9 ml.kg−1.km−1) during the shod condition. There was no difference in substrate utilization between conditions. The barefoot condition elicited a smaller centre of mass vertical displacement (1.24±0.14 cm vs. 1.34±0.17 cm). At a natural walking speed, barefoot walking is more economical than shod walking at the same velocity in children. The higher energy cost of shod walking should be considered when evaluating the use of footwear by children.
Keywords: physiology; paediatrics; footwear; gait